Effect of Na/Al and Si/Al ratios on adhesion strength of geopolymers as coating material - Irfan Khan, M. (Trans Tech Publications Ltd, 2014)
In this study fly ash based aluminosilicate coatings were formulated and the effect of the Na/Al, Si/Al ratios, and curing time upon adhesion strength of geopolymeric coating was measured using Elcometer 108. Geopolymer gained their maximum adhesion within first three days. After 3 days curing on 60oC resulted into a maximum adhesion strength of 10MPa at Si/Al=3 and Na/Al=1.0. Micro structural analysis and Infra red spectroscopy was used to study the geopolymerisation process. Surface profile of fly ash particles shown that degree of reactivity has a direct relation with their surface roughness. Â© 2014 Trans Tech Publications, Switzerland.